2014
DOI: 10.4084/mjhid.2014.042
|View full text |Cite
|
Sign up to set email alerts
|

Iron Chelation Therapy With Deferasirox in the Management of Iron Overload in Primary Myelofibrosis

Abstract: Deferasirox (DSX) is the principal option currently available for iron-chelation-therapy (ICT), principally in the management of myelodysplastic syndromes (MDS), while in primary myelofibrosis (PMF) the expertise is limited. We analyzed our experience in 10 PMF with transfusion-dependent anemia, treated with DSX from September 2010 to December 2013. The median dose tolerated of DSX was 750 mg/day (10 mg/kg/day), with 3 transient interruption of treatment for drug-related adverse events (AEs) and 3 definitive d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…Conversely, there were scarce and erratic data concerning the use of DFX in patients with FP-MPN and transfusional iron overload prior to this report (14,15). Similar observations to those presented in our data set have been observed in some case reports (10,(14)(15)(16)(17) and more recently in a small singlecenter study (18). However, these studies are small and therefore have a limited potential impact on clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…Conversely, there were scarce and erratic data concerning the use of DFX in patients with FP-MPN and transfusional iron overload prior to this report (14,15). Similar observations to those presented in our data set have been observed in some case reports (10,(14)(15)(16)(17) and more recently in a small singlecenter study (18). However, these studies are small and therefore have a limited potential impact on clinical practice.…”
Section: Discussionsupporting
confidence: 85%
“…Whether this improvement is caused by the reduction of oxidative stress and DNA damage due to ICT with deferasirox or another deferasirox-mediated effect is unclear [18,20]. The patient, however, reported no other drug intake, and we consider this to be further evidence of improved hematopoiesis with ICT leading to sustained transfusion independence as described in several case reports in patients with primary myelofibrosis [2,5,12,13,14,15,18]. Restoration of trilineage hematopoiesis with ICT with deferasirox was also described in several patients with aplastic anemia [12,23,24].…”
Section: Discussionmentioning
confidence: 56%
“…However, for patients with myeloproliferative syndromes, especially PMF, no clear benefit of chelation therapy has been shown [12]. Current treatment guidelines in PMF do not recommend ICT in patients with transfusion dependency and iron overload [1], although an increasing number of publications indicate possible positive effects on hematopoiesis and also possible transfusion independency during ICT with deferasirox [2,9,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…Myelofibrosis (MF) is a clonal myeloproliferative neoplasm with a high prevalence of transfusion‐dependent (TD) anaemia, which may lead to iron overload (IOL) (Tefferi et al , ). At present, very few data are available on the role of iron chelation therapy (ICT) with deferasirox (DFX) in MF (Elli et al , ; Latagliata et al , ). In this study, we assessed the efficacy of DFX, in terms of iron chelation response (ICR), haematological improvement (HI), impact on survival and leukaemic evolution, on 45 consecutive MF patients fulfilling the inclusion criteria (Data S1).…”
Section: Clinical and Laboratory Variables At Baseline According To mentioning
confidence: 99%
“…Our preliminary data open new insights regarding the benefit of DFX in MF patients with TD anaemia. Several emerging lines of evidence indicated that DFX can improve haematopoiesis, however, these data come from single case descriptions (Di Tucci et al , ; Piro et al , ) or small retrospective studies (Elli et al , ; Latagliata et al , ). DFX, probably independently of its iron‐chelating property but through the interference on its reactive oxygen species (ROS) signalling activation, may influence key factors involved in self‐renewal/differentiation of haematopoietic stem cells (HSC; Zhang et al , ).…”
Section: Clinical and Laboratory Variables At Baseline According To mentioning
confidence: 99%